Taking Care of Our Own : When Family Caregivers Do Medical Work - Mong, Sherry N., 1961- (Book collections on Project MUSE., 2020)
"Drawing on interviews with family caregivers and nurses, this book explores the labor processes that occur when caregivers learn and implement skilled nursing procedures."--